PENDIDIKAN KELUARGA DI ERA MERDEKA BELAJAR - FIRDA WAHDANI; Hamam Burhanuddin (Pendidikan Agama Islam, 2020)
Family is most important places in instilling education for children, the family will create a desirable generation, parents become one of the important factors in education, inattention of parents to children will cause children to become neglected in their education, children deserve the love from parents and full attention. In 2045 Indonesia will get a demographic bonus where the productive age is more than the non-productive, this will be very closely related to the current education, especially education in the family environment needs to be prepared carefully related to strategy and implementation. By applying the concept of free learning in the family environment as an effort to help children in solving learning difficulties, correcting bad behavior and habits, as well as providing reinforcement in the intellectual and spiritual realms. it is expected that education in Indonesia can become more advanced, of quality, and can give birth to a golden generation that is resilient in facing various challenges in the future.